THE EFFECT OF ASEAN-CHINA FREE TRADE AREA ON INDONESIA-CHINA TEXTILE PRODUCTS INTRA-INDUSTRY TRADE - Sadat, Dea Nuriry (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2025)
Purpose This research investigates the relationship between the ASEAN-China Free Trade Area (ACFTA) and Indonesia-China Intra-industry Trade (IIT) and identifies other IIT determinants as controlled variables, such as the economic size gap, trade openness, trade imbalance, and COVID-19 conditions Design/methodology/approach This study uses the panel data method and applies the Grubel and Lloyd index to measure the IIT index Findings The main finding of this study demonstrates a different angle from most other studies, estimating that the agreement negatively and significantly affects the horizontal and lower sides of vertical IIT and the upper side of vertical IIT Research limitations/implications The primary challenge of this study is the availability of data on foreign direct investment (FDI), which is commonly used in previous literature Originality/value The contribution of this study to the extant empirical works is threefold. First, the focus is on textile products since most IIT studies are limited to manufactured goods. Second, the study decomposes IIT into HIIT, UVIIT, and LVIIT, while most studies only focus on HIIT and VIIT. Finally, this article provides another perspective on variable interest analysis and attempts to shed deeper insight into the ACFTA-IIT relationship that other studies might not discuss